Enhanced arabinose utilization by adaptively evolved Klebsiella pneumoniae enables efficient 2,3-butanediol production from sugar beet pulp - Dhodduraj, Kawinharsun; Narisetty, Vivek; Nabavi, Seyed Ali; Coulon, Frederic; Maity, Sunil K.; Kumar, Vinod (Royal Society of Chemistry (RSC), 2026)
Fermentative production of 2,3-butanediol (BDO) offers a sustainable alternative to fossil-based chemical synthesis, but its economic feasibility strongly depends on the use of low-cost feedstocks and efficient microbial strains capable of utilizing mixed sugars. In the current study, Klebsiella pneumoniae was used to produce BDO from arabinose and glucose-rich fractions derived from sugar beet pulp (SBP), a major sugar industry waste. Initial shake-flask studies revealed efficient BDO formation from arabinose, although fermentation performance was declined at higher concentrations (60 g L−1) due to substrate inhibition. The strain was subjected to adaptive laboratory evolution (ALE) to overcome this limitation. The evolved strain (A4) showed enhanced arabinose utilization and achieved a productivity of 0.54 g L−1 h−1 at 100 g L−1 arabinose compared with 0.43 g L−1 h−1 for the parent strain. The fed-batch bioreactor cultivation of the evolved strain resulted in BDO titers of 84.9 and 96.7 g L−1 with a conversion yield of 0.39 g g−1 using arabinose- and glucose-rich mixture of pure sugars, respectively. During fed-batch cultivation, the strain accumulated 82.2 and 92.4 g L−1 BDO from arabinose- and glucose-rich SBP hydrolysates, respectively, with a conversion yield of 0.38 g g−1. The pasteurization of SBP hydrolysates significantly improved fermentation kinetics, which resulted in the shortening of fermentation times by 30–40 h while maintaining the BDO titer and yield comparable to the non-pasteurized hydrolysate. Overall, BDO production from pure sugars and sugar-rich hydrolysates from SBP was similar. These results demonstrate the immense potential of the isolate K. pneumoniae as a biofactory in valorizing SBP into BDO with possibility for future industrialization.
Keywords: 34 Chemical Sciences; 40 Engineering; Pneumonia & Influenza; Pneumonia; Lung; Infectious Diseases; 12 Responsible Consumption and Production; 3406 Physical chemistry; 4004 Chemical engineering; 4008 Electrical engineering